2010
DOI: 10.1029/2009jc005348
|View full text |Cite
|
Sign up to set email alerts
|

Sediment transport under wave groups: Relative importance between nonlinear waveshape and nonlinear boundary layer streaming

Abstract: [1] Sediment transport under nonlinear waves in a predominately sheet flow condition is investigated using a two-phase model. Specifically, we study the relative importance between the nonlinear waveshape and nonlinear boundary layer streaming on cross-shore sand transport. Terms in the governing equations because of the nonlinear boundary layer process are included in this one-dimensional vertical (1DV) model by simplifying the two-dimensional vertical (2DV) ensemble-averaged two-phase equations with the assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…Table 3 summarizes the model coefficients. These coefficients were shown to work well for typical medium to coarse sand transport Yu et al, 2010;Cheng et al, 2017a). Furthermore, it was found that the coefficient B (see Eq.…”
Section: Mixing Length (1-d Only)mentioning
confidence: 85%
See 2 more Smart Citations
“…Table 3 summarizes the model coefficients. These coefficients were shown to work well for typical medium to coarse sand transport Yu et al, 2010;Cheng et al, 2017a). Furthermore, it was found that the coefficient B (see Eq.…”
Section: Mixing Length (1-d Only)mentioning
confidence: 85%
“…Turbulence model Particle stress Asano (1990), Li and Sawamoto (1995), and Dong and Zhang (2002) mixing length Bagnold Jenkins and Hanes (1998) mixing length kinetic theory Revil-Baudard and Chauchat (2013) mixing length granular rheology Li et al (2008) k − L Bagnold Bakhtyar et al (2009) k − ε Bagnold , Chauchat and Guillou (2008), and Amoudry et al (2008) k − ε kinetic theory Yu et al (2010) and Cheng et al (2017a) Amoudry (2014 and Bombardelli (2009, 2010) k − ω kinetic theory Lee et al (2016) k − ε granular rheology is modeled by the fluctuation energy of the particle phase (or granular temperature). Various models were developed to model the granular temperature.…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the reasons why two-phase flow models have become widely used to investigate sediment transport under the sheet flow regime (e.g., [1][2][3][4][5]). Another important aspect of the two-phase framework for sediment transport is its ability to represent the coupled fluid sediment system continuously from within the stationary bed throughout the entire bottom boundary layer (see for example the explanatory diagrams in [6][7][8]).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of boundary layer streaming [Dohmen-Janssen and Hanes, 2002;Nielsen, 2006;Yu et al, 2010] and of groundwater in/exfiltration [Turner and Masselink, 1998], which affect net sediment transport, are not included in the model. For example, groundwater infiltration induces a net downward force on sediment grains (counteracting sediment mobilization) but also decreases the boundary thickness, increasing the shear stress (enhancing sediment mobilization) [Butt et al, 2001].…”
Section: Model Developmentmentioning
confidence: 99%